Predictors of attendance and barriers to cataract surgery in Kenya, Bangladesh and the Philippines. (September 2013) - Syed, Alishbah; Polack, Sarah; Eusebio, Cristina; Mathenge, Wanjiku; Wadud, Zakia; Mamunur, A. K. M.; Foster, Allen; Kuper, Hannah
Abstract Purpose: Cataract is the leading cause of blindness worldwide, and is particularly common in low- and middle-income countries. Our study aims to identify the predictors for and barriers to acceptance of cataract surgery in Kenya, Bangladesh and the Philippines. Methods: Cases were individuals aged ≥50 years and with best corrected VA of <6/24 in the better eye due to cataract who were identified through population-based surveys and community-based case detection. Cases were asked why they had not attended for surgery. They were offered free cataract surgery and followed-up at one year. Non-acceptors were interviewed to identify barriers to accepting surgery. Results: Of all participants, 58.6% attended for cataract surgery in Kenya, 53.9% Bangladesh and 47.1% the Philippines. Younger age was a predictor for attendance for surgery in all three countries. In Bangladesh and Kenya, male gender and psychosocial score were predictors. At baseline "cost" and "unaware of cataract" were most frequently reported barriers to uptake of surgery in the three settings. At follow-up, "surgical services inaccessible" was one of the two most frequently reported barriers in Kenya and the Philippines while "fear" was most frequently reported in Bangladesh and the Philippines. There were no consistent predictors of the most frequently reported barriers across the different settings. Conclusions: Future services need to focus on increasing uptake among older people and women. Cost is often reported as a barrier but this may conceal more complicated underlying barriers which need to be explored through in-depth qualitative research. Implications for Rehabilitation Cataract is the leading cause of blindness worldwide, and is particularly common in low- and middle-income countries. Evidence suggests that even when surgical services are available, there can be a lack of demand and low utilization resulting from barriers to uptake. Older cataract patients, females and especially older females are least likely to attend for surgery. Future cataract surgical programmes should put special emphasis on targeting and increasing uptake in these groups.